Dental Health Education at Aisyiyah Kindergarten, Kalitengah Village: Edukasi Kesehatan Gigi Di Taman Kanak-Kanak Aisyiyah Desa Kalitengah (Indonesian Journal of Cultural and Community Development, 2024)
Dental and oral health is an important part of overall body health. Problems with teeth and mouth can negatively impact body health and interfere with daily activities, especially in children. Dental health education at Aisyiyah Kindergarten in Kalitengah Village is crucial for raising children's awareness of the importance of oral hygiene. This educational activity includes outreach on proper tooth brushing techniques, understanding the significance of dental health, and providing information on foods that are beneficial or harmful to teeth. Through a fun and interactive approach, children are encouraged to actively participate in tooth brushing practices and selecting healthy foods. The results of this activity indicate an increase in children's understanding of dental health, which is expected to foster good habits from an early age to maintain their dental health in the future